Effects of Multiwalled Carbon Nanotube Surface Modification and Purification on Bovine Serum Albumin Binding and Biological Responses. (24th October 2016) - Bai, Wei; Wu, Zheqiong; Mitra, Somenath; Brown, Jared M.
Abstract : Carboxylation of multiwalled carbon nanotubes (MWCNTs) has been used to improve solubility in aqueous systems and for further functionalization with biologically active moieties for biomedical uses. An important consideration is that oxidation debris is generated during the process of carboxylation, which can be removed by base washing. We hypothesized that surface modification as well as purification by debris removal may alter physicochemical properties of MWCNTs and their ability to bind proteins. We utilized pristine MWCNT, carboxylated MWCNTs (F-MWCNTs), and base-washed carboxylated MWCNTs (BW-F-MWCNTs) to examine formation of a bovine serum albumin (BSA) protein corona and impact on biological responses. We found that carboxylation increased the capability of F-MWCNTs to bind BSA, and base washing further increased this binding. Functionalization increased cellular uptake by rat aortic endothelial cells (RAEC) and mouse macrophages (RAW264.7), while base washing showed results similar to the functionalized analog. Interestingly, BSA binding downregulated mRNA levels of interleukin-6 (IL-6) and heme oxygenase 1 (Hmox1) in RAEC cells but upregulated the expression of IL-6 and Hmox1 in RAW264.7 cells. Overall, our study demonstrated that surface modification as well as further purification impacted the interaction of MWCNTs with proteins and subsequent cellular responses.